DEVICE CONTROL USING PLCC: AN EMBEDDED SYSTEM APPROACH - Mr. Prasad P. Telharkar; Miss Dhanashree S. Kale (International Journal of Innovations in Engineering Research and Technology, 2021)
Home power consumption tends to grow in proportion to the increase in the number of large-sized electric home appliances. An embedded system without any new additional wiring has been developed for home power management. By using Power Line Communication (PLC) technology, electric home appliances can be controlled and monitored through domestic power lines. We describe a PPCOM (PLC Power-Controlled Outlet Module) which integrates the multiple AC power sockets, the power measuring module, the PLC module and a microcontroller into a power outlet to switch the power of the sockets on/off and to measure the power consumption of plugged-in electric home appliances. We are also designing an embedded home server which supports the Web page user interface, thus allowing the user to easily control and monitor the electric home appliances by means of the Internet. In addition, the field experiments reported have demonstrated that our design can be practically implemented and provides adequate results.